Application of the Proactive Molecular Risk Classifier for Endometrial Cancer (ProMisE) to patients conservatively treated: Outcomes from an institutional series. (September 2019) - Falcone, Francesca; Normanno, Nicola; Losito, Nunzia S.; Scognamiglio, Giosuè; Esposito Abate, Riziero; Chicchinelli, Nicoletta; Casella, Gennaro; Laurelli, Giuseppe; Scaffa, Cono; Greggi, Stefano
Abstract: Objective: To test the Proactive Molecular Risk Classifier for Endometrial Cancer (ProMisE) and determine the frequency of specific/prognostic molecular alterations within a cohort of endometrial cancer (EC) women conservatively treated by combined hysteroscopic resection and progestin therapy. Study design: We used blocks of formalin-fixed paraffin-embedded tissue from the primary tumors of patients enrolled into the ECCo trial (EudraCT 2010-018581-23) between 2007 and 2016. In order to assign EC resectoscopic specimens to one of four ProMisE subgroups, testing involved sequential assessment of i) immunohistochemistry (IHC) for mismatch repair (MMR) proteins MLH1, MSH2, MSH6 and PMS2; ii) sequencing for POLE/POLD1 exonuclease domain mutations (EDMs); iii) p53 IHC. Results: Molecular analysis methods were used in 25 patients (stage IA, G1-2 endometrioid EC), of whom 15 (60%) represented fully evaluable cases. Seven cases (46.7%) had abnormal MMR IHC, POLE/POLD1 EDMs were found in 3 cases (20%), and abnormal p53 IHC in 1 case (6.6%). Three patients (20%) had more than one molecular feature. Among 10 (40%) 'unclassifiable' patients, six failures in achieving complete molecular categorization were due to the low tumor volume. Molecular classification of the 15 fully evaluable cases yielded the following ProMisE subtypes: 7 (46.7%) MMR IHC abnormal, 1 (6.6%) POLE EDM, 0 (0%) p53 IHC abnormal, 7 (46.7%) p53 IHC wild-type. Conclusions: Although larger series are needed to further assess the feasibility of a molecular categorization in a fertility-sparing setting, data presented are promising. In women with early stage low-volume disease, operative hysteroscopy could be advantageous to provide samples allowing complete genetic risk assessment.